Time-Dependent Spectra during Radiative Decay of Singlet Excitons in Conjugated Polymers. (31st January 2015) - Chen, Ren-ai; Jiang, De-Yao; Li, Sheng; George, Thomas F.
Abstract : Excited states in a conjugated polymer are associated with excitation, relaxation, diffusion and decay processes, and their dynamical properties can be used to fabricate polymeric optoelectronic devices with higher efficiency. Although the timescale of excitonic radiative decay has been narrowed less than a nanosecond, the nonadiabatic mechanism presented in this article is able to provide a detailed depiction of the fluorescence dynamics with respect to singlet exciton decay and the evolution of the dipole moment. Simultaneously, it is found that the lifetime of the singlet exciton ranges from around 500 picoseconds to one nanosecond, which is in line with recent experimental observations on polymers such as benzothiadiazole and thiophene.